La crítica intelectual pagana al monacato primitivo - Jiménez Sánchez, J. A. (Sacris erudiri, 2010)
The criticism that the intellectual pagan elites directed against the early monasticism was originated by causes which were more complex than the strictly religious ones. Therefore, we must speak of antimonastic criticism, not antichristian criticism, caused by cultural, political and social motives. The authors who censured the monasticism — Julianus, Libanius, Eunapius, Palladas, Rutilius Namatianus and Zosimus — criticised the monks for their hypocrisy, as they simulated virtue, but they hid behind their black cloaks to perpetrate all the evildoings they wanted; their misanthropy, which opposed to the Hellenic-Roman philanthropy, and supposed the refusal of the social responsibilities of man; and for not being useful neither to war nor to the State, as they were not allowed to engender new citizens. Moreover, these pagan authors accused them of being traitors to the Roman Empire and of representing an evident danger to the classical cultural inheritance.